Musik,sociokulturella betingelser och musikundervisning - Bouij, Christer (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1990)
Music's social function is to create group identity and a sense of community, either by inclusion (common traits) or exclusion (distinguishing traits). Variations in the understanding of musical functions can be plotted along the axis anthropological -- aesthetic. Anthropological perspective is applied more commonly to oral traditions and in popular education whereas the aesthetic approach is rooted in academic and scribal practices. The official aims of education (syllabuses, curricula, etc.) are implemented by local authorities according to varying notions of "good music", "musicality" and of music's role in the development of the individual, i.e. somewhere between Björkvold's ngoma (music as an integral part of living) and absolute music aesthetics (intramusical norms for standard music education). This view is also supported by Vulliamy's four basic paradigms of strategies for music education. Music's social connotations are strongly felt by teacher and pupil alike. Society is always present even when the school music room door is closed.